Path following of unmanned quadrotor using improved 3D limit-cycle navigation - Fajril Akbar (Kulliyyah of Engineering, International Islamic University Malaysia, 2014)
Quadrotor is one of rotary wing type UAV with four rotors in cross configuration. It has the capability to perform incredibly however the flight path effective planning is vital together with avoiding obstacle along its path. It needs to be equipped with path planning algorithm to reach its target in a minimum amount of time and following the settled target precisely, as well as avoiding any obstacles in its path. Limit-cycle navigation method is one of the solutions for obstacles avoidance in mobile robot application. The extension of limit-cycle navigation into Three Dimensions (3D), made it possible to be applied by aerial vehicle for obstacle avoidance. The extended limit-cycle has been introduced, but it does not show the effectiveness in planning the flight path. In this research, rendering the obstacle region into a cylinder with a half of sphere on top would generate the efficient path and provide the best way in avoiding a stationary obstacle. By assuming the obstacle information is known in advance, a simulation and performance study is done using limit-cycle characteristic method. The simulation results show that the generated path was successfully avoided with different obstacle conditions. The simulation results of the proposed method compared with previous methods show maximum efficiency in travelling distance of 68.60%. Arducopter with GPS waypoint was used to verify the usability of the proposed design for real system application. Arducopter's hardware-in-loop test shows that the generated path could be tracked with maximum cross track error of 1.993 meters. This implies that this improvement on 3D limit-cycle method can successfully plan a safe flight path for quadrotor.